Health Services for Buruli Ulcer Control: Lessons from a Field Study in Ghana - Ackumey, Mercy M.; Kwakye-Maclean, Cynthia; Ampadu, Edwin O.; de Savigny, Don; Weiss, Mitchell G. (PLOS Neglected Tropical Diseases, 2011)
Author Summary Buruli ulcer (BU), caused by Mycobacterium ulcerans infection, is a debilitating disease of the skin and underlying tissue which starts as a painless nodule, oedema or plaque and could develop into painful and massive ulcers if left untreated. Using a combination of quantitative and qualitative methods, the study assessed the effectiveness of the BUPaT programme to improve early detection and management of BU in an endemic area in Ghana. The results of the study showed extensive collaboration across all levels, (national, municipality and community), which contributed to strengthening the programme. Health staff were trained to manage all BU cases. School teachers, municipal environmental staff and community surveillance volunteers were trained to give the right health messages, screen for detection of early cases and refer for medical treatment. WHO-recommended antibiotics improved treatment and cure, particularly for early lesions, and prevented recurrences. Improving access to antibiotic treatment is critical for early case management. Health education is required to emphasise the effectiveness of treatment with antibiotics to reduce deformities and the importance of seeking medical treatment for all skin lesions. Further research is needed to explain the role of environmental factors in BU contagion.